A rapid review of evidence to inform an ear, nose and throat service delivery model in remote Australia - Susan Jacups; Irina Kinchin (James Cook University, 2021)
Introduction: This rapid literature review aimed to inform the development of a new sustainable, evidence-based service delivery model for ear, nose and throat (ENT) services across Cape York, Australia. This work seeks to investigate the research question: 'What are the characteristics of successful outreach services which can be applied to remote living Indigenous children?' Methods: A comprehensive search of three major electronic databases (PubMed, CINAHL and MEDLINE) and two websites (HealthInfo Net and Google Scholar) was conducted for peer-reviewed and grey literature, to elicit characteristics of ENT and hearing services in rural and remote Australia, Canada, New Zealand and the USA. The search strategy was divided into four sections: outreach services for rural and remote communities; services for Indigenous children and families; telehealth service provision; and remote ear and hearing health service models. A narrative synthesis was used to summarise the key features of the identified service characteristics. Results: In total, 71 studies met the inclusion criteria and were included in the review, which identified a number of success and sustainability traits, including employment of a dedicated ear and hearing educator; outreach nursing and audiology services; and telehealth access to ENT services. Ideally, outreach organisations should partner with local services that employ local Indigenous health workers to provide ongoing ear health services in community between outreach visits. Conclusion: The evidence suggests that sound and sustainable ENT outreach models build on existing services; are tailored to local needs; promote cross-agency collaboration; use telehealth; and promote ongoing education of the local workforce.